1996
DOI: 10.1021/jp9604498
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Radicals on a Metal Surface from Photoinduced Dissociation of Physisorbed Molecules:  CH2 from H2CO on Ag(111)

Abstract: Submonolayer formaldehyde (H 2 CO) has been photodissociated on Ag(111) at 35 K using nanosecond 287 nm laser pulses. The low temperature prohibits further bimolecular reactions of the dissociation products and allows their analysis by electron energy loss spectroscopy. One of the dissociation products has been identified as the radical species methylene (CH 2 ). The dissociation is induced by photoexcited substrate electrons attached to formaldehyde, forming a transient formaldehyde negative ion that dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…This picture is based on the results of Fleck et al who found that the cross section for polymerization, which is also attributed to H 2 CO (a) -formation, increases rapidly above the measured threshold of 3.1 ( 0.2 eV. 14,15 The tunneling probability will increase with increasing photon energy up to the vacuum level at 4.4-4.5 eV, 15,16 beyond which free electrons can be generated which can directly scatter and attach to an adsorbed formaldehyde molecule. A qualitative measure of the internal energy of the desorbing formaldehyde molecules can be obtained from Figure 5, where the ion time-of-flight mass spectrum for formaldehyde molecules desorbed by 266 nm light (140 µJ/cm 2 ) is compared to a roomtemperature gas-phase sample.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…This picture is based on the results of Fleck et al who found that the cross section for polymerization, which is also attributed to H 2 CO (a) -formation, increases rapidly above the measured threshold of 3.1 ( 0.2 eV. 14,15 The tunneling probability will increase with increasing photon energy up to the vacuum level at 4.4-4.5 eV, 15,16 beyond which free electrons can be generated which can directly scatter and attach to an adsorbed formaldehyde molecule. A qualitative measure of the internal energy of the desorbing formaldehyde molecules can be obtained from Figure 5, where the ion time-of-flight mass spectrum for formaldehyde molecules desorbed by 266 nm light (140 µJ/cm 2 ) is compared to a roomtemperature gas-phase sample.…”
Section: Methodsmentioning
confidence: 81%
“…34 Specifically, the Antoniewicz-DIET model 34,35 involving the formation and decay of a temporary negative ion provides a reasonable description since Fleck et al have shown that polymerization most likely proceeds via a DEA process involving the H 2 CO (a) -anion . [14][15][16] In the Antoniewicz model, "hot" subsurface electrons produced by UV excitation of the metal substrate resonantly scatter into the lowest unoccupied level (2π*) of the adsorbate (formaldehyde). The 2π* level is estimated to lie ∼1 eV below the vacuum level.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, adsorbed CH 2 has been observed experimentally [16] and analyzed theoretically [17] as a product of formaldehyde photodissociation on Ag (1 1 1); NH x fragments adsorbed on Ag(1 1 1) have been detected under electron-induced NH 3 decomposition [18]; OH groups formed by the reaction of surface oxygen and hydrogen have been observed by X-ray photoelectron spectroscopy in Ref. [4] and in the theoretical study of epoxidation and combustion of propene [19]; Hbond formation with the CH group on Ag(1 0 0) surface has been studied in Ref.…”
Section: Introductionmentioning
confidence: 99%